Cytokine‐ and chemokine‐induced inflammatory colorectal tumor microenvironment: Emerging avenue for targeted therapy - Ajaz A. Bhat (12984701) (2022)
Colorectal cancer (CRC) is a predominant life-threatening cancer, with liver and peritoneal metastases as the primary causes of death. Intestinal inflammation, a known CRC risk factor, nurtures a local inflammatory environment enriched with tumor cells, endothelial cells, immune cells, cancer-associated fibroblasts, immunosuppressive cells, and secretory growth factors. The complex interactions of aberrantly expressed cytokines, chemokines, growth factors, and matrix-remodeling enzymes promote CRC pathogenesis and evoke systemic responses that affect disease outcomes. Mounting evidence suggests that these cytokines and chemokines play a role in the progression of CRC through immunosuppression and modulation of the tumor microenvironment, which is partly achieved by the recruitment of immunosuppressive cells. These cells impart features such as cancer stem cell-like properties, drug resistance, invasion, and formation of the premetastatic niche in distant organs, promoting metastasis and aggressive CRC growth. A deeper understanding of the cytokine- and chemokine-mediated signaling networks that link tumor progression and metastasis will provide insights into the mechanistic details of disease aggressiveness and facilitate the development of novel therapeutics for CRC. Here, we summarized the current knowledge of cytokine- and chemokine-mediated crosstalk in the inflammatory tumor microenvironment, which drives immunosuppression, resistance to therapeutics, and metastasis during CRC progression. We also outlined the potential of this crosstalk as a novel therapeutic target for CRC. The major cytokine/chemokine pathways involved in cancer immunotherapy are also discussed in this review.  Other Information Published in: Cancer Communications License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/cac2.12295